Armed groups and the balance of power the international relations of terrorists, warlords and insurgents - Vinci, Anthony (LSE international studies, 2009)
Offers a framework for understanding the international relations of armed groups, including terrorist organizations, insurgencies and warlords. This book argues that such groups are empirically sovereign non-state actors that are motivated by the pursuit of power and exist as part of an anarchic, self-help system.